Environmental Conditions Affecting Iron Sulfides Reactivity and Transformation of Iron Oxyhydroxide Compounds - H. Lara, Rene; Mallet, Martine; A. Escobedo, Miguel; Ramirez-Aldaba, Hugo (Current Inorganic Chemistry (Discontinued), 2015)
Oxidation of iron sulfide minerals (mainly pyrite and pyrrhotite) occurs in mine waste and other mining environments which is a natural process associated to weathering reactions and produced by waste spillage due to eolic or pluvial dispersion. Iron sulfides environmental weathering results in secondary sulfur and iron (III) oxyhydroxides (IOH’s) formation whose mineralogical transformation affects iron sulfides reactivity inducing sulfides passivation and/or enhanced mineral reactivity. Review reports considering IOH’s dynamic behavior are sparse and barely found. In this review work, authors up-date iron sulfides weathering and IOH’s relationship and also include some original and experimental data, aiming to establish main IOH’s occurrence and stability during iron sulfides weathering under environmental conditions in mining environments.
Keywords: mining environments